The satisfaction level of patients with trauma on pain management - (:unkn) unknown (ORTADOGU AD PRES & PUBL CO, 2007)
Objective: This is a descriptive study to determine patient satisfaction of pain relief exercises in trauma patients. Material and Methods: The study group consisted of patients who presented with trauma to the emergency units of two hospitals in Istanbul. A total of 418 patients aged 18-65 years were included. A 13-item individual properties form, shortened wound assessment with visual analog scale and forth section of McGill-Melzack pain question form were used to collect data. Data were expressed as percentage, median, and standart deviation, and One-way Anova Test, Student's t Test, and Pearson Corelation Analysis methods were used for statistical analyses. Results: Of the patients, 25.4% (n= 106) was in the 28-37 years age range, 69.9% (n= 292) was male, 70.8% (n= 296) was graduate of elementary school, 44.5% (n= 186) was self-employed, 94.5% (n= 395) had blunt trauma and 75.4% (n= 315) had limb trauma. All (n= 418) patients were administered nonsteroid antiinflammatory drugs; 95.5% (n= 416) by intramuscular injection; in 62.9% (n= 293) the paint did not relieve. Conclusion: The pain perceived after trauma until interview time was defined as very severe by 51.7% (n= 216) of the patients, The pain relief exercises were considered not satisfactory by 63.4% (n= 265) of the cases; the degree of satisfaction for patient care in the emergency unit was medium (4.35 +/- 2.78; 5.18 +/- 2.07). As a result, pain severity increased parallel to trauma severity and the degree of satisfaction for pain relief exercises and emergency care for patients who had very severe pain severity was low. The data obtained suggest that pain is still not managed as a serious problem in the emergency trauma units and that most trauma patients are not satisfied with the emergency care and pain relieving approaches.
Keywords: pain measurement; patient satisfaction; multiple trauma; POSTOPERATIVE PAIN; ANALGESIC USE; EXPECTATIONS; EMERGENCY; PATTERNS